2020
DOI: 10.3390/ma13194251
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of a Clayey Soil with Ladle Metallurgy Furnace Slag Fines

Abstract: The research study described in this paper investigated the potential to use steel furnace slag (SFS) as a stabilizing additive for clayey soils. Even though SFS has limited applications in civil engineering infrastructure due to the formation of deleterious expansion in the presence of water, the free CaO and free MgO contents allow for the SFS to be a potentially suitable candidate for clayey soil stabilization and improvement. In this investigation, a kaolinite clay was stabilized with 10% and 15% ladle met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 87 publications
3
16
0
4
Order By: Relevance
“…The total content of SiO 2 and Al 2 O 3 is greater than 95%. Many studies illustrated that the combination of NaOH and Na 2 SiO 3 solutions could be the best choice for the polymerization of aluminosilicate sources [11,17,22] because NaOH could dissolve aluminosilicate sources and Na 2 SiO 3 continuously, providing more Na + and Si 4+ for polymerization. However, great difficulties in the transit and storage of NaOH and Na 2 SiO 3 solutions and ecological environment protection are always likely to be encountered in engineering practices.…”
Section: ) Gbmentioning
confidence: 99%
See 1 more Smart Citation
“…The total content of SiO 2 and Al 2 O 3 is greater than 95%. Many studies illustrated that the combination of NaOH and Na 2 SiO 3 solutions could be the best choice for the polymerization of aluminosilicate sources [11,17,22] because NaOH could dissolve aluminosilicate sources and Na 2 SiO 3 continuously, providing more Na + and Si 4+ for polymerization. However, great difficulties in the transit and storage of NaOH and Na 2 SiO 3 solutions and ecological environment protection are always likely to be encountered in engineering practices.…”
Section: ) Gbmentioning
confidence: 99%
“…Various studies have employed GB to enhance the properties of problematic soils. Brand et al [17] found that the unconfined compressive strength (UCS) and dynamic modulus of clayey soil, relative to the untreated case, could be increased by 91 and 221% when 15% of ladle metallurgy furnace (LMF) slag was used. Jiang et al [18] studied the effects of rice husk ash (RHA) on silty clay (SC) stabilization and reported that the optimum dosage of RHA was 2, 4, and 6% when the content of CaO was 3, 5, and 7%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Steel slag is the most cost-effective material for improving weak subgrade soil (Akinwumi 2014;Patel and Patel 2016). The study by (Brand et al 2020) investigates the potential use of steel slag for stabilizing clay soil. As a result, when 15% steel slag is mixed with soil, the unconfined compressive strength increases by 91%, implying that steel slag can be used effectively as a soil stabilization mixture.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it leads to the appearance of the foundation's imperfections threatening the whole overlaying constructions status, varying from minor defects to the collapse of the construction due to the foundation's failure. According to the following authors [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]28,39,[47][48][49][50][51], these factors could be sorted as Collapsible/Metastable soil, Liquefiable Soil, Expansive soil, Slope instability, seismic impact, seasonal variation of ground water level, and other natural geological and environmental reasons [52][53][54][55][56][57][58][59][60] • Industrial (technical) reasons: summarized as complex factors caused by engineering errors, such as inadequate preliminary design, insufficient or incorrect geotechnical investigations, poor quality of construction work, violation of building codes, and poor soil compaction during the construction process. In addition, there are aspects related to changes in the capacity concerning a particular project, the poor quality of the construction materials, reconstruction processes, cities planning and developments, the insufficient distance between the adjacent foundations, vibration effect of the neighborhood construction equipment, the changes in the groundwater level due to inappropriate seepage network, and other factors.…”
Section: Introductionmentioning
confidence: 99%